A software engineering approach for access control to multi-level-security documents - Ahmad, M. (IGI Global, 2013)
Access control to multi level security documents is very important and challenging issue. Millions of organizations around the globe intend to apply security levels over their confidential documents to protect from unauthorized use. Some numbered access control approaches have been proposed and an optimal solution is the need of the time. This chapter presents an overview of a robust software engineering approach for access control to multi-level security documents. The access control system incorporates stages including data refinement, text comprehension, and understanding of multi-stage protection and application levels. It will scan the document, tag the sections of certain text, understand the meaning of various levels, group-up the text using bottom-up approach, and then classify the levels as per protection norms (set as organization wise) defined. This approach will be very helpful for multi-level protection of precious information. Only authorized users would be able to access the information relevant to them as defined by the authorities. Â© 2013, IGI Global.